Placental malperfusion in response to intrauterine inflammation and its connection to fetal sequelae - Eloundou, Solange N. (PLoS One, 2019)
Exposure to intrauterine inflammation (IUI) is associated with short- and long-term adverse perinatal outcomes. However, little data exist on utilizing placenta to prognosticate fetal injury in this scenario. Our study aimed to utilize imaging modalities to evaluate mechanisms contributing to placental injury following IUI exposure and correlated it to concomitant fetal brain injury. CD1 pregnant dams underwent laparotomies and received intrauterine injections of either lipopolysaccharide (LPS; a model of IUI) or phosphate-buffered saline (PBS). In utero ultrasound Doppler velocimetry of uterine and umbilical arteries and magnetic resonance imaging (MRI) of placental volumes with confirmatory immunohistochemical (vimentin) and histochemistry (fibrin) analyses were performed. ELISA for thrombosis markers, fibrinogen and fibrin was performed to analyze thrombi in placenta. Fetal brain immunohistochemistry was performed to detect microglial activation (ionized calcium-binding adaptor molecule 1, Iba1). On ultrasound, LPS group demonstrated elevated resistance indices, pulsatility indices and a greater occurrence of absent end-diastolic flow in the umbilical and uterine arteries. In the fetus, there was an increased cardiac Tei indices in the LPS group. MRI revealed decreased volume of placenta in the LPS group associated with placental thinning and placental endothelial damage on immunohistochemistry. Decreased fibrinogen content and more thrombi staining in placenta exposed to maternal LPS indicated the hypercoagulability. Furthermore, the expression of Iba1was significantly associated with placental thickness (r = -0.7890, Pearson correlation coefficient). Our data indicate that IUI can trigger events leading to maternal placental malperfusion and fetal vessel resistance, as well as predispose the developing fetus to cardiac dysfunction and brain damage. Furthermore, our data suggest that prenatal ultrasound can be a real-time clinical tool for assessing fetal risk for adverse neurologic outcomes following the potential IUI exposure.